Management of early breast cancer with breast conserving treatment : Evaluation of cases in Yogyakarta - T. Aryandono T. Aryandono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Background: Breast conserving treatment (BCT) can be done for early breast cancer, with the same survival as mastectomy. The patients should not lost the breast resulted from the treatment. Objective: To evaluate the patients with breast conserving treatment in two hospitals in Yogyakarta, in connection with locoregional recurrence, distant metastasis, cosmetic result and general condition. The results can be used for improving the technique of breast conserving treatment in this region. Methods: Five patients with BCT from 1996 until 2001 were treated with wide excision (lumpectomy), axillary dissection level I and II, and radiotherapy 5000 cGy. Histopathological examination, estrogen and progesterone receptor and c-erbB-2 examination were conducted for these patients. All patients received hormonal adjuvant treatment with tamoxifen, no one received adjuvant chemotherapy.Results: The age range was 28-51 years old, stage one, maximum diameter of tumor was 1.5 cm. Most of them were invasive duct carcinoma, with positive ER, PR and c-erbB-2. Follow up from 8 to 66 months, with median follow up 37 months. No locoregional recurrences, one with distant metastasis (lung). The cosmetic result as well as the general condition were good.Conclusions: Breast conserving treatment had been done on patients and resulted in good cosmetic result, no locoregional recurrences and good general condition. With early detection and good patient selection, the patient should have not lost the breast with the same survival as in mastectomy.Keywords: breast conserving treatment- lumpectomy - radiotherapy - estrogen receptor - progesterone receptor.